2022
DOI: 10.1002/adhm.202102791
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Multifunctional Black Phosphorus Hydrogel with Antibacterial and Antioxidant Properties: A Stepwise Countermeasure for Diabetic Skin Wound Healing

Abstract: Cutaneous wound healing, especially diabetic wound healing, is a common clinical challenge. Reactive oxygen species (ROS) and bacterial infection are two major detrimental states that induce oxidative stress and inflammatory responses and impede angiogenesis and wound healing. A derivative of the metabolite itaconate, 4-octyl itaconate (4OI) has attracted increasing research interest in recent years due to its antioxidant and anti-inflammatory properties. In this study, 4OI-modified black phosphorus (BP) nanos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(63 citation statements)
references
References 54 publications
0
56
0
Order By: Relevance
“…Another study demonstrated that the lignin-CuS nanocomposites incorporated PVA hydrogel exhibit peroxidase-like performance and phototherapeutic actions [ 143 ]. In some formulations, the photothermal agents act as carriers and protect PSs excretion, ultimately enabling rapid wound closure via protecting endothelial and promoting neovascularization [ 144 ].…”
Section: Films Scaffolds and Hydrogelsmentioning
confidence: 99%
“…Another study demonstrated that the lignin-CuS nanocomposites incorporated PVA hydrogel exhibit peroxidase-like performance and phototherapeutic actions [ 143 ]. In some formulations, the photothermal agents act as carriers and protect PSs excretion, ultimately enabling rapid wound closure via protecting endothelial and promoting neovascularization [ 144 ].…”
Section: Films Scaffolds and Hydrogelsmentioning
confidence: 99%
“…7B). 107 To endow BP nanosheets with antioxidant and anti-inflammatory activities, 4-octyl itaconate (4OI) was modified onto the surface of BP nanosheets, and then 4OI functionalized black phosphorus was embedded into a gelatin methacryloyl (GelMA) hydrogel for the management of diabetic wound infection. With the aid of a laser, the 4OI-BP gel precursor solution enabled fast gelation and formed a protective film on open wounds, and simultaneously exerted photodynamic/photothermal therapy to combat bacterial infection.…”
Section: Stimuli-responsive Systemsmentioning
confidence: 99%
“…Unfortunately, many previous reports were at the stage of “ proof of concept ”; they did not conform strictly to a specific application. According to the papers we have screened, major flaws in our current reporting on developing antibacterial surfaces for implantable medical devices are ( Table 7 includes some typical examples [ 18 , 272 , 273 , 274 , 275 , 276 , 277 , 278 ]) (1) many reports are lack of comprehensive understanding of the requirements of a specific application or even have no clear indication of use (Cases 2, 3, 7, and 8 in Table 7 ); as a result, it is hard to ensure the effectiveness and safety of such designs because the incidence and pathogens of DAIs are site-specific [ 66 ] and the biocompatibility of biomaterials is referred to specific applications [ 279 ]. (2) Some reports choose testing assays that do not closely relate to the intended use.…”
Section: Directions To Improve the Quality Of Antibacterial Reportsmentioning
confidence: 99%